Pengaruh Profitabilitas, Ukuran Perusahaan, Struktur Aset, Risiko Bisnis dan Likuiditas pada Struktur Modal - Nita Septiani, Ni Putu; Suaryana, I Gusti Ngurah Agung (E-Jurnal Akuntansi; Vol 22 No 3 (2018), 2018)
Each company must have the same primary goal that is to maximize the value of the company. To be able to maximize the value of the company, one of the ways that companies need to do is produce an optimal capital structure. Based on the study of theory and previous research results, the capital structure can be influenced by profitability, firm size, asset structure, business risk and liquidity. Therefore, companies should consider the above factors when establishing their capital structure in order to produce an optimal capital structure. This study aims to examine empirically the effect of profitability, firm size, asset structure, business risk and liquidity in the capital structure. This research was conducted on the property and real estate company period 2013-2015 listed in Indonesia Stock Exchange, with samples taken as many as 27 companies out of a total population of 48 companies. The sample in this research was determined by purposive sampling method using a criterion. Data were collected using non-participant observation. The data analysis technique used is the Multiple Linear Regression Analysis. Based on the results of the analysis concluded that firm size has a positive effect on capital structure, where the increase in firm size will also increase the capital structure. The structure of assets and liquidity negatively affect the capital structure, where an increase in asset structure and liquidity will decrease the capital structure. Meanwhile, profitability and business risk have no effect on capital structure. Keywords: Capital structure, profitability, firm size, asset structure, business risk, liquidity